Town and country associations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
a seminar was held in Senegal from 26 to 28 January 2000 on 'Rural-urban interactions: the flows and organisation of resources'.